Sugammadex: A Scientific Review Including Safety and Efficacy, Update on Regulatory Issues, and Clinical Use in Europe. (July 2015) - Jahr, Jonathan S.; Miller, John E.; Hiruma, Jessica; Emaus, Katie; You, Michelle; Meistelman, Claude
Abstract : Muscle relaxants are used in the perioperative period to aid in endotracheal intubation, facilitate surgical exposure, and in the critical care setting for prolonged relaxation. Until now, the only mechanism to reverse their effect is acetylcholinesterase inhibitors that result in excess parasympathetic activity and require the second drug to prevent this side effect. Additionally, the onset and degree of neuromuscular antagonism are often unpredictable and unreliable. Sugammadex is the first of the cyclodextrins to be used as a therapeutic agent. It quickly, effectively, and safely reverses steroidal neuromuscular blockers by encapsulating the muscle relaxant and rendering it inactive. Sugammadex may be considered the ideal reversal agent and the first drug in its class, which will likely change the practice of anesthesia and clinical neuromuscular pharmacology.